Emerging trends in neuromodulation for schizophrenia: A global bibliometric analysis - Nurfaizatul Aisyah, Ab Aziz; Siti Atiyah, Ali; Nor Asyikin, Fadzil; Zamzuri, Idris; Sabarisah, Hashim (Neurotak Publishing, 2024)
The utilization of neuromodulation techniques is increasingly capturing the attention of researchers and clinicians as potential non-pharmaceutical interventions for treating schizophrenia, especially among drug-resistant schizophrenia patients. Assessing the existing landscape of research activity and identifying gaps in neuromodulation-schizophrenia research is crucial for strategic planning and guiding future research in this domain. This bibliometric analysis paper aims to discern the publications and research trends in neuromodulationschizophrenia studies spanning 2019 to 2023.The Scopus database search was performed using the related keywords. Neuromodulation-schizophrenia-related publications were retrieved from the Scopus database from 2019 to 2023. Bibliometric analyses were performed using Harzing's Publish or Perish, Microsoft Excel and VOS viewer software programs.Three hundred fifty-three publications from the Scopus database were retrieved and analyzed to answer the research questions. The highest number of publications, 87, was observed in 2022. The United States led the way in publishing neuromodulationschizophrenia research with 96 articles. Keyword analysis revealed that "transcranial direct current stimulation"(tDCS) and "transcranial magnetic stimulation"(TMS) were the most prevalent neuromodulation techniques investigated in schizophrenia research. Transcranial-focused ultrasound (TUS) emerged as a novel and current neuromodulation technique explored in treating schizophrenia, as indicated by the analysis of selected journal articles.This bibliometric paper provides insights intothe current status, knowledge base, and future directions of neuromodulation-schizophrenia studies, which will serve future researchers in focusing on applyingneuromodulation techniquesas potential non-pharmaceutical interventions for schizophrenia